Kedudukan Yuridis dan Kekuatan Pembuktian Dokumen Elektronik Sebagai Alat Bukti Tulisan dalam Perkara Wanprestasi - Anggi Sri Haryati Simarmata; Jordan Lenbert Pandiangan; Muhammad Fajna Iqbal (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the juridical status and evidentiary strength of electronic documents as written evidence in breach of contract disputes within the Indonesian legal system through a normative legal research approach. The analysis employs statute and conceptual approaches to assess the coherence between conventional civil procedural law and contemporary electronic transaction regulations, particularly focusing on the Indonesian Civil Code, HIR/RBg, and the Law on Electronic Information and Transactions along with its implementing regulations. The findings indicate that electronic documents have obtained formal legal recognition as valid evidence; however, their evidentiary weight remains contingent upon authentication, integrity, and reliability standards embedded in electronic systems. The study further identifies normative inconsistencies and interpretative disparities in judicial practice, which create legal uncertainty in evaluating electronic evidence. By applying systematic and teleological interpretation, this research proposes a harmonized legal framework grounded in the principle of functional equivalence to bridge the gap between traditional and digital evidentiary regimes. The study contributes to the development of modern evidentiary law by offering a prescriptive model that integrates legal norms and technological validation mechanisms to ensure legal certainty, fairness, and procedural efficiency